CHARACTERISTICS OF CHRONIC SUPPURATIVE OTITIS MEDIA SUFFERERS AT WAIKABUBAK HOSPITAL - Gustina Maryanti Mooy; Sylvia Sylvia (Jurnal Health Sains, 2023)
Chronic suppurative otitis media (CSOM) is one of the most common ear diseases in developing countries, one of which is Indonesia. CSOM is the stage of middle ear disease where there is chronic inflammation of the middle ear and mastoid and tympanic membrane that is not intact (perforation) and found secretions (otorrhea), purulent intermittent, said to be chronic if the disease is intermittent or persists for 2 months or more. Prevalence surveys around the world, show the incidence of CSOM is 65-330 million sufferers with watery ears where 60% of them have conductive hearing loss. This is an important issue for dealing with deafness in developing countries. This study aims to determine the distribution of CSOM sufferers at Waikabubak Hospital in September 2022 – February 2023 based on age, sex, side of the ear infected and type of otorrhea. This research was conducted at the ENT-KL Clinic at Waikabubak Hospital in February 2023 using secondary data from the patient register book. There were 85 CSOM patients recorded in September 2022 - February 2023. The most common incidence happen in adult age 26-45 years old with the number of 30 patients (35.3%). CSOM is more common in women than men with an the number of incidence 43 patients (50.6%). Based on the side of the ear infected with CSOM, it was more common on the unilateral side, with the number of 72 patients (84.7%) and based on the type of otorrhea, the active type was more frequent, with the number of 67 patients (78.8%).